Analisis Pengaruh Kompetensi Manajer Proyek terhadap Keberhasilan Proyek Kontruksi Transportasi Jalan Rel di Sumatera Bagian Barat - Vianda, Rendi; Jumas, Dwifitra; Anif, Bahrul; Peli, Martelius; Fuadi, Al Busyra; Ariani, Vivi (Jurnal Talenta Sipil, 2024)
The role of a project manager is a crucial factor that influences project success. To achieve project success, it is necessary to have project managers who possess the appropriate competencies to carry out their tasks. Respondents in this study are individuals who are directly involved and responsible for the implementation of railway projects in West Sumatra Province, totaling 61 people. Data collection was done by administering questionnaires to the research respondents. The data analysis used descriptive analysis to summarize and describe the data, while multiple linear regression was used to understand the relationship between independent variables (knowledge, skills, attitudes, behavior) and dependent variables (project success). Based on the analysis results, it can be concluded that factors such as knowledge, skills, attitudes, and behaviors have a significant impact on the success of railway projects in West Sumatra. The skill factor of project managers is the most dominant factor influencing the level of project success, with a contribution of 23.8%.